Twelve and a half : leveraging the emotional ingredients necessary for business success - Vaynerchuk, Gary (New York, NY : Harper Business, 2021)
"In his sixth business book, bestselling author, entrepreneur, and investor Gary Vaynerchuk explores the twelve essential emotional skills that are integral to his life-and business-success and provides today's (and tomorrow's) leaders with critical tools to acquire and develop these traits"--
Includes bibliographical references.
Keywords: Success in business; Leadership